Early Attentional Capture of Animate Motion: 4-Year-Olds Show a Pop-Out Effect for Chasing Stimuli. (March 2019) - Hofrichter, Ruth; Rutherford, M. D.
Preferential attention to animate motion develops early in life, and adults and infants are particularly attuned to chasing motion. Adults can detect chasing objects among up to 10 distractors and are better at detecting a chase among nonchasing distractors than a nonchase among chasing distractors. We tested whether an attentional preference for chasing has developed by the age of 4, and whether 4-year-olds can explicitly point out chasing objects. On a touch screen, participants were shown a chasing pair of circles among a varying number of distractors (2, 4, 6, 8, 10). Participants had to touch the chaser. Reaction time for adults or 4-year-olds was independent of distractor numbers, consistent with a pop-out effect for chasing stimuli. As early as 4 years of age, children show a pop-out effect for chasing objects and can identify them via touch.